X+26-18x=4(2-x)

Simple and best practice solution for X+26-18x=4(2-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+26-18x=4(2-x) equation:


Simplifying
X + 26 + -18x = 4(2 + -1x)

Reorder the terms:
26 + X + -18x = 4(2 + -1x)
26 + X + -18x = (2 * 4 + -1x * 4)
26 + X + -18x = (8 + -4x)

Solving
26 + X + -18x = 8 + -4x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-26' to each side of the equation.
26 + X + -26 + -18x = 8 + -26 + -4x

Reorder the terms:
26 + -26 + X + -18x = 8 + -26 + -4x

Combine like terms: 26 + -26 = 0
0 + X + -18x = 8 + -26 + -4x
X + -18x = 8 + -26 + -4x

Combine like terms: 8 + -26 = -18
X + -18x = -18 + -4x

Add '18x' to each side of the equation.
X + -18x + 18x = -18 + -4x + 18x

Combine like terms: -18x + 18x = 0
X + 0 = -18 + -4x + 18x
X = -18 + -4x + 18x

Combine like terms: -4x + 18x = 14x
X = -18 + 14x

Simplifying
X = -18 + 14x

See similar equations:

| -q=-2q+16 | | .25g-1=2 | | 8/×+10=4/2x-7 | | 2(x)+2(6+2x)= | | -4n-16n=-20 | | -3(f+18)=-12 | | y+1/5y | | 13.98-17.6t-18.37=7.37-15.2t | | 13.98-17.6t-1.37=7.37-15.2t | | 15x^4+65x^3+60x^2=0 | | -5.78-7j=-5.7j+11.25 | | 18.75+18d=12.67+17.6d | | 5/8•16/20 | | 18.4y-5.96=9.24+2.8y+16.4y | | 5.5p=8.85+6p | | r-20=4+6-4r | | 9x^3+42x^2-15x=0 | | 14/8=n/4 | | 13-9b=-6b-17 | | 11n=12n-18 | | 7k+10=9k | | 9/x+3-5/x-3=5x/x^2-9 | | (5k-6)/4=-5 | | -1-2f=6-f | | 10+8u-1=10u-7 | | Cos(37=11/x | | 5(3p+1)=50 | | 80x^2+52x+8=0 | | 9x+2/7x=6/7-4/x | | 3(3a+9)=0 | | 9x-.2y=4 | | -7x-6-7x=-118 |

Equations solver categories